2010
DOI: 10.1007/s10840-010-9484-6
|View full text |Cite
|
Sign up to set email alerts
|

Implantable cardioverter defibrillators confer survival benefit in patients with renal insufficiency but not in dialysis-dependent patients

Abstract: Randomized clinical trials have demonstrated that the implantable cardioverter defibrillator (ICD) reduces mortality in heart failure patients with reduced systolic function but have excluded patients with advanced chronic kidney disease (CKD). We investigated the impact of ICDs on survival in patients with moderate-to-severe CKD, including those requiring dialysis therapy (DT). Patients followed at our institution between 1998 and 2008 with left ventricular ejection fraction (LVEF)< or =35% and CKD, defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Three studies were obtained from a previously published patient-level meta-analysis. 10) Finally, 11 eligible studies 7,8,[11][12][13][18][19][20][21][22][23] from 9 articles [10][11][12][13][18][19][20][21][22] were included. The search steps are illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies were obtained from a previously published patient-level meta-analysis. 10) Finally, 11 eligible studies 7,8,[11][12][13][18][19][20][21][22][23] from 9 articles [10][11][12][13][18][19][20][21][22] were included. The search steps are illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The search steps are illustrated in Figure 1. Characteristics of included studies: Eleven studies 7,8,[11][12][13][18][19][20][21][22][23] enrolled 20,196 CKD patients (4,178 patients receiving ICD therapy and 16,018 patients in the control groups), and the duration of the studies ranged from 12 months to 96 months. There were 5 studies 11,18,19,21,22) involving 18,149 patients on dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, no randomized clinical trials have been performed in this area. Khan et al reported the impact of ICDs on survival in 78 patients with advanced CKD of whom 45 patients were on dialysis (Khan et al, 2010). In the dialysis cohort, ICD therapy did not impact survival whereas in CKD patients not on dialysis, survival was significantly better in patients with an ICD (2-year survival 80% versus 54%; p=0.027).…”
Section: Role Of Implantable Cardioverter Defibrillator For Primary Pmentioning
confidence: 99%